The Physical Properties and The Extractive Content of Sugar Palm Stem (Arenga pinnata) - Muhdi; Hartono, Rudi; Nainggolan, John Parulian (Talenta Publisher, 2019)
This study aims to determine the physical and chemical properties of sugar palm. Physical properties include moisture content, density, and shrinkage from wet to dry oven chemical properties included of extractive solubility in cold and wet solutions. The samples were 15 years of age and originated from Sidikalang, Dairi district, North Sumatra. Three individual samples were taken and cut into 50 cm of length of three types of height namely base, middle, and end. The research was also conducted horizontally (edge, center, and at the core). The results of this study indicated that the average water content was 120.31-603.48%, the specific weight was 0.12-0.51 g/cm3, and the shrinkage from wet to dry oven was 28.06-77.69%. The extractive solubility in cold water was 11.66-87.22%, while in hot water was 10-90%. Based on the specific weight/density obtained, the outer part or edge of the palm sugar was included in the strength classes IV and V.